2018
DOI: 10.1007/s00268-018-4612-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Surgery for Mid‐Transverse Colon Cancer: Laparoscopic Extended Right Hemicolectomy Versus Laparoscopic Transverse Colectomy

Abstract: Laparoscopic extended right hemicolectomy and laparoscopic transverse colectomy offer similar oncological outcomes for mid-transverse colon cancer. Laparoscopic extended right hemicolectomy might be associated with fewer postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(64 citation statements)
references
References 34 publications
(29 reference statements)
3
59
2
Order By: Relevance
“…Imaging the vascular pattern preoperatively via biphasic CT angiography has been shown to be an efficient way of avoiding creating TA B L E 2 Patient factors and tumour characteristics 200 (17) 125 (11) Abbreviations: ASA, American Society of Anesthesiologists physical status classification; EC, extended colectomy; NR, not reported; SC, segmental colectomy.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging the vascular pattern preoperatively via biphasic CT angiography has been shown to be an efficient way of avoiding creating TA B L E 2 Patient factors and tumour characteristics 200 (17) 125 (11) Abbreviations: ASA, American Society of Anesthesiologists physical status classification; EC, extended colectomy; NR, not reported; SC, segmental colectomy.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%
“…Segmental colectomy for tumours of the distal transverse colon and splenic flexure was similarly defined as resection of a length of transverse colon and proximal descending colon with ligation of the supplying middle colic vessels at its origin and where required ligation of the left colic vessel[13,14]. Extended colectomy included both left and right extended colectomy[2,5,[10][11][12]14] and sub-total colectomy[13]. All studies were published between 2013 and 2020.Overall a total of 3395 patients were included in the final analysis.Enrolment of patients spanned over29 years (1989-2018).…”
mentioning
confidence: 99%
“…However, the optimal surgical approach remains unclear for the treatment of transverse colon cancer, and it is often based on the surgeon’s preference whether to perform an extended colectomy or a transverse colectomy. In several retrospective studies for patients with transverse colon cancer, it was [ 15 , 16 ] demonstrated that there were no differences between an extended colectomy and a transverse colectomy in terms of postoperative risk and oncological outcomes, and concluded that a segmental resection may be considered as an option for the treatment of localized tumors of the transverse colon. Theoretically, Toyota et al [ 6 ] found that for 24 patients (45.2%) with lymph node metastasis who were identified among the 53 patients with right-transverse colon cancer, there was no lymph node metastasis at the root of the ileocolic artery.…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative bowel function has been studied in some studies. Matsuda et al noted that the time to first flatus (median: 2 days) and time to resumption of liquid diet (median: 4 days) was similar in both the treatment arms 15 . Similarly, Leijssen et al found that postoperative ileus developed in 12.5% patients in both the groups 14 …”
Section: Literature Reviewmentioning
confidence: 92%